Vygotsky’s Legacy on Teaching and Learning Writing as Social Process - Sitti Nurfaidah (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
Vygotsky has imprinted many influences on learning and teaching learning development. Although his main works focus on psychological aspects of children’s learning, it is very useful both for the teachers and researchers in understanding and exploring the best they can do for the development of the children’s learning. One of Vygotsky’s legacy can be traced in the process of teaching and learning writing in which this skill is regarded as social process. Scholars believe that his idea on sociohistorical perspective becomes the foundation in giving scaffolding in teaching writing, collaborative work activity in writing lesson, as well as teacher reflection on his teaching and learning activities in the classroom, as much as the teaching and learning writing as social process. This article, therefore, represents review on how Vygotsky’s influences on language learning and teaching development, particularly in writing which is considered as social process.